Suicides following inpatient psychiatric hospitalization: A nationwide case control study - Winkler, Petr; Mladá, Karolína; Csémy, Ladislav; Nechanská, Blanka; Höschl, Cyril (Journal of affective disorders, 2015)
BACKGROUND: Research shows the elevated risk of suicide associated with current or recent inpatient psychiatric hospitalization. However, it is unclear whether this applies in the area of post-communist Central and Eastern Europe where mental health care has not been deinstitutionalized yet. The present study aims to examine the rates of suicides among psychiatric patients during and shortly after discharge from inpatient hospitalization in the Czech Republic. METHODS: All inpatient psychiatric hospitalizations and all suicides committed between 2008 and 2012 have been merged on an individual data basis. The time horizon between the admission and two months after the discharge from inpatient psychiatric facility was utilized and multiple logistic regression was performed to calculate the odds of committing suicide. RESULTS: A total of 137,290 inpatients were hospitalized in Czech psychiatric facilities between 2008 and 2012, and 402 of the inpatients committed suicide during the hospitalization or within the 2 months after the discharge. Highly elevated risks of suicides were found to be associated with being a male, having a history of multiple hospitalizations, and having a diagnosis of affective, anxiety, or personality disorder. LIMITATIONS: Limitations are related to the design of the study, and its reliance on routinely collected data. Also, it was not possible to assess the odds of suicide associated with inpatient psychiatric hospitalization against the odds of suicide in general population. CONCLUSIONS: During psychiatric treatment and recovery, suicial behavior and idealiation is increased. In psychiatry, hospitalization may be a risky period for suicide behavior. Suicide rates during and soon after the psychiatric hospitalization identified in this study from Central and Eastern Europe are similar to the findings from Western Europe. Preventive strategies should be tailored accordingly.
Keywords: Sex Factors; poruchy nálady; Personality Disorders; Humans; Case-Control Studies; Hospitals, Psychiatric; lidé středního věku; Suicide; Central and Eastern Europe; studie případů a kontrol; socioekonomické faktory; poruchy osobnosti; Female; Aged; mladý dospělý; dospělí; výsledek terapie; senioři; lidé; hospitalizace; propuštění pacienta; Mood Disorders; sexuální faktory; Socioeconomic Factors; duševní poruchy; Anxiety Disorders; Adult; ústavy pro duševně nemocné; sebevražda; ženské pohlaví; Psychiatric Department, Hospital; Inpatients; Hospitalization; Male; Middle Aged; Psychiatric hospitalization; hospitalizovaní pacienti; úzkostné poruchy; sebevražedné myšlenky; Adolescent; Czech Republic; Treatment Outcome; psychiatrické oddělení nemocnice; Mental Disorders; Young Adult; Case control study; Česká republika; mužské pohlaví; Patient Discharge; mladiství; Suicidal Ideation